APPLICATION PROGRAM PURCHASE CAR RESERVATIONS BY PHONE WITH VISUAL BASIC - Nurritu Praworo; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2004)
Application of computers in handling the transaction report is required because of the leadership and employees of the report can make decisions to achieve corporate objectives and also to simplify the search for the desired data and the data are not quickly lost or damaged. every company has their own way in dealing with sale and purchase transaction reports car reservations, in terms of how big or small a company. In data processing performed by the company will be better controlled as well as fast and easy to do, so little mistakes that can occur. to make the car buying and selling orders report writer made application buying and selling cars booking program, which was created by using Visual Basic